Determining the magnitude of treatment effects in strength training research through the use of the effect size - Rhea, M. R. (The Journal of Strength and Conditioning Research, 2004)
In order to improve the applicability of research to exercise professionals, it is suggested that researchers analyze and report data in intervention studies that can be interpreted in relation to other studies. The effect size and proposed scale for determining the magnitude of the treatment effect can assist strength and conditioning professionals in interpreting and applying the findings of the strength training studies.